Razvoj varovanja avtorskih in sorodnih pravic pred spletnimi kršitvami - Kuzma, Dominik (Podjetje in delo, 2015)
The authors discuss problems regarding mass copyright infringements over the Internet. Besides describing the current situation in Slovenia, the authors also introduce the basics of the technologies used for infringement (BitTorrent, P2P, downloading, streaming), their mode of operations and relating legal consequences. By describing the German legal solution of the problem which, although quite similar to the Slovenian legislation, allows efficient prosecution of the copyright infringement, authors discus the minimum legal amendments of the Slovenian legislature necessary in order to enable effective copyright protection. Such amendments would constitute firstly of balancing the privacy right, held by the offender, with the copyright holder's right to be protected by enacting the conditions under which personal data of infringements can be collected, saved and passed over to the authors. This arrangement would enable civil prosecution of individual infringements in cases where no criminal offense has been made, that is currently de facto impossible. Secondly, the exemptions from prohibition of making copies in force for the audio and video works should be synchronized with those of software works.
Keywords: avtorske pravice; avtorsko pravo; kršenje; pravno varstvo; spletne strani; svetovni splet